The moonday letters - Itäranta, Emmi, 1976- (Titan Books, 2022)
An effortlessly rich and lyrical mystery wrapped in a love story that bends space, time, myth and science, perfect for fans of Octavia Butler and Emily St. John Mandel. Sol has disappeared. Their Earth-born wife Lumi sets out to find them but it is no simple feat: each clue uncovers another enigma. Their disappearance leads back to underground environmental groups and a web of mystery that spans the space between the planets themselves. Told through letters and extracts, the course of Lumi's journey takes her not only from the affluent colonies of Mars to the devastated remnants of Earth, but into the hidden depths of Sol's past and the long-forgotten secrets of her own. Part space-age epistolary, part eco-thriller, and a love story between two individuals from very different worlds.